Lithium ion secondary battery

By setting the negative electrode current collector and groove with chromium element content on the negative electrode sheet of the lithium-ion secondary battery, and combining the 1,4-dicyano-2-butene in the electrolyte, the corrosion problem of negative electrode current collector is solved, and the high-temperature cycling and rate performance improvement of the battery is achieved.

CN119786701AActive Publication Date: 2025-04-08ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411994896.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

While improving the high-temperature cycle and rate performance, existing lithium-ion secondary batteries are difficult to improve the corrosion problem of negative electrode current collectors, resulting in a degradation of battery performance.

Method used

By setting a negative electrode current collector with a chromium element content of 10-300 ppm on the negative electrode sheet and setting a groove on the surface of the negative electrode active layer, the content of 1,4-dicyano-2-butene in the electrolyte is between 0.01%-5%, and the product of the groove depth and the content of 1,4-dicyano-2-butene is within the range of 0.0005-1.75 to slow down the oxidative corrosion of the negative electrode current collector.

Benefits of technology

Effectively slow down the oxidative corrosion of the negative electrode current collector, improve its tensile strength, prevent fracture, and improve the battery's magnification and high-temperature cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786701A_ABST
    Figure CN119786701A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and discloses a lithium ion secondary battery. The lithium ion secondary battery comprises a negative electrode plate and electrolyte, the negative electrode plate comprises a negative electrode current collector and a negative electrode active layer, the chromium content in the negative electrode current collector is within 10-300 ppm, and a groove with the depth of H [mu] m is formed in the surface, away from the negative electrode current collector, of the negative electrode active layer; the electrolyte comprises 1, 4-dicyano-2-butene with the content of 0.01%-5%, and E * H is larger than or equal to 0.0005 and smaller than or equal to 1.75. By controlling the content of the chromium element in the negative current collector to be within the range, the current collector can be ensured to have good conductivity and corrosion resistance; on the basis, the value of E * H is regulated and controlled, on one hand, the oxidation corrosion rate of the negative electrode current collector can be slowed down, the tensile strength of the negative electrode current collector is improved, the negative electrode current collector is prevented from being broken, and on the other hand, it can be ensured that the battery has high multiplying power and high-temperature cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] In lithium-ion secondary batteries, in order to improve the energy density of lithium-ion secondary batteries, one of the commonly used methods in the industry is to increase the gram capacity of the negative electrode active material. Silicon materials are often used as negative electrode active materials due to their high theoretical gram capacity. However, silicon particles are prone to volume expansion during the lithium-ion charging and discharging process, which leads to the destruction of the internal structure of the negative electrode material, seriously affecting the life and stability of the battery. At present, the stability of the negative electrode sheet can be improved by adding 1,4-dicyano-2-butene to the electrolyte. At the same time, the presence of 1,4-dicyano-2-butene can also improve the high-temperature cycle and storage performance of the battery. However, 1,4-dicyano-2-butene will have a certain corrosive effect on the negative electrode current collector, which not only reduces the conductivity of the current collector, increases the overall internal resistance of the battery, and affects the rate performance of the battery, but also causes the mechanical properties of the copper foil to deteriorate, and even break, thereby affecting the performance of the battery. Summary of the invention

[0003] In view of this, the present application provides a lithium-ion secondary battery, which aims to solve to a certain extent the problem that existing lithium-ion secondary batteries cannot improve the corrosion of the negative electrode collector while improving high-temperature cycle and rate performance.

[0004] According to an embodiment of the present application, a lithium-ion secondary battery is provided, comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte;

[0005] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side of the surface of the negative electrode current collector; the negative electrode current collector comprises a chromium element, and the content of the chromium element is Cppm, 10≤C≤300, based on the mass of the negative electrode current collector; a groove is arranged on the surface of the negative electrode active layer away from the negative electrode current collector, and the depth of the groove is Hμm;

[0006] The electrolyte includes 1,4-dicyano-2-butene. Based on the mass of the electrolyte, the content of the 1,4-dicyano-2-butene is E, 0.01%≤E≤5%; and the following conditions are satisfied: 0.0005≤E*H≤1.75.

[0007] In some optional embodiments, 0.005≤E*H≤1.5.

[0008] In some optional embodiments, 5≤H≤35.

[0009] In some optional embodiments, 200≤C / E≤3×10 6 .

[0010] In some optional implementations, at least one of the following conditions is met:

[0011] a. 10≤C≤100;

[0012] b. 0.1% ≤ E ≤ 4.3%;

[0013] c. 233≤C / E≤10 5 .

[0014] In some optional embodiments, the negative electrode sheet is provided with a recessed area with an opening toward the separator, the recessed area includes a tab groove and a tab paper groove; along the thickness direction of the negative electrode sheet, the tab paper groove is higher than the tab groove to form a step surface, and the tab paper is provided on the step surface, and the tab paper covers the tab groove;

[0015] In the thickness direction of the negative electrode sheet, the thickness T3 of the negative electrode active layer is ≥ the depth T1 of the tab tape groove, and the depth T1 of the tab tape groove is ≥ the thickness T2 of the tab protective tape.

[0016] And / or, in the length direction of the negative electrode sheet, the width W1 of the tab tape groove is ≥ the width W2 of the tab tape, and the width W2 of the tab tape is ≥ the width S of the tab groove.

[0017] In some optional embodiments, the length direction of the groove is parallel to the width direction of the negative electrode sheet, the number of the grooves is at least 2, and the distance between two adjacent grooves is L, 0.5 mm ≤ L ≤ 2 mm;

[0018] The width S of the tab groove satisfies: 6mm≤S≤15mm, and 3≤S / L≤30.

[0019] In some optional embodiments, the distance between the junction of the tab groove and the negative electrode active layer and the groove is G1, 0<G1≤5mm.

[0020] In some optional embodiments, the distance between the end of the groove and the edge of the negative electrode active layer is G2, 0<G2≤5mm.

[0021] In some optional embodiments, the negative electrode active layer includes a first active layer and a second active layer stacked, the first active layer is located between the negative electrode current collector and the second active layer, and the ratio of the thickness of the second active layer to the total thickness of the negative electrode active layer is x, 0.1≤x≤0.5;

[0022] The first active layer includes a first negative electrode active material, the first negative electrode active material includes a first graphite, and the median particle size Dv501 of the first graphite is 12 μm-20 μm;

[0023] The second active layer includes a second negative electrode active material, the second negative electrode active material includes a second graphite, and the median particle size Dv502 of the second graphite is 5 μm-12 μm;

[0024] Satisfies: Dv501>Dv502.

[0025] In some optional embodiments, the first negative electrode active material and / or the second negative electrode active material further comprises a silicon-based material. Based on the mass of the first negative electrode active material or the second negative electrode active material, the content of the silicon-based material is D, satisfying: 0.2≤D / E≤3000, 0.01%≤E≤5%.

[0026] In some optional embodiments, the D is 1%-30%.

[0027] In some optional embodiments, the D is 3%-30%, the E is 0.1%-4.3%, and 0.7≤D / E≤300.

[0028] In some optional embodiments, the charging cut-off voltage of the lithium-ion secondary battery is ≥4.48V.

[0029] The technical solution of this application has the following advantages:

[0030] The lithium ion secondary battery provided by the present application comprises a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side of the surface of the negative electrode current collector; the negative electrode current collector comprises a chromium element, and the content of the chromium element is Cppm based on the mass of the negative electrode current collector, 10≤C≤300; a groove is arranged on the surface of the negative electrode active layer away from the negative electrode current collector, and the depth of the groove is Hμm; the electrolyte comprises 1,4-dicyano-2-butene, and the content of the 1,4-dicyano-2-butene is E based on the mass of the electrolyte, 0.01%≤E≤5%; and the following conditions are satisfied: 0.0005≤E*H≤1.75. The present application has found that when the chromium content in the negative electrode collector is in the range of 10-300ppm, the negative electrode collector can be ensured to have good conductivity and corrosion resistance; on this basis, by adjusting the groove depth H on the negative electrode sheet and the content E of the electrolyte additive 1,4-dicyano-2-butene to meet E*H in the range of 0.0005-1.75, on the one hand, the rate of oxidation corrosion of the negative electrode collector can be slowed down, the tensile strength of the negative electrode collector can be improved, and the negative electrode collector can be prevented from breaking; on the other hand, it can also ensure that the battery has a higher rate and high temperature cycle performance.

[0031] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0033] Figure 1 It is a schematic diagram of the structure of a negative electrode sheet in one embodiment of the present application.

[0034] Figure 2 It is a partial cross-sectional schematic diagram of a negative electrode sheet in one embodiment of the present application.

[0035] Figure 3 yes Figure 1 A partial enlarged view of .

[0036] The reference numerals are described as follows:

[0037] 1. Negative electrode current collector; 2. Negative electrode active layer; 3. Groove; 4. Tab groove; 5. Tab; 6. Tab tape groove; 7-Step surface. DETAILED DESCRIPTION

[0038] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0039] It should be noted that the terms "inside" and "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0040] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0041] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0042] First of all, it should be noted that at high potential, the 1,4-dicyano-2-butene additive in the electrolyte can participate in the formation of the SEI film on the negative electrode surface, stabilize the electrode-electrolyte interface, and effectively improve the high-temperature cycle and high-temperature storage performance of the battery. Unfortunately, this application study found that the process of 1,4-dicyano-2-butene participating in the construction of the SEI film will cause oxidative corrosion to the negative electrode current collector, resulting in a decrease in the mechanical properties of the negative electrode current collector or even fracture.

[0043] In order to improve the corrosion resistance of the negative electrode current collector, the common practice is to plate chromium on the surface of the negative electrode current collector to form a passivation layer. The higher the chromium content on the negative electrode current collector, the better the corrosion resistance, but at the same time it will affect the conductivity of the negative electrode current collector.

[0044] Using laser to process lines (or "grooves") of a certain depth and width on the surface of the negative electrode sheet can increase the contact area between the negative electrode sheet and the electrolyte, which is beneficial to the infiltration of the electrolyte and makes the electrochemical reaction more complete, thereby increasing the capacity and energy density of the battery. At the same time, it can also shorten the migration distance of lithium ions in the negative electrode sheet and increase the charge and discharge rate of the battery.

[0045] The research of this application found that in the process of laser scribing, the energy emitted by the laser is not only absorbed by the negative active layer, but also absorbed by the negative current collector, resulting in the destruction of the passivation layer on the surface of the negative current collector (such as copper foil). As the laser intensity increases, the groove depth increases. At the same time, the more laser energy is absorbed by the negative current collector, the greater the degree of damage to the passivation layer, and even the copper foil. The damaged negative current collector will be oxidized when it undergoes the charge and discharge process. On the one hand, it reduces the conductivity of the negative current collector, resulting in an increase in the overall internal resistance of the battery. On the other hand, it reduces the thickness of the negative current collector, affecting its tensile strength.

[0046] In order to solve the above problems existing in the related art, the present application provides a lithium ion secondary battery, including a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte;

[0047] The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector;

[0048] The negative electrode current collector includes a chromium element, and the content of the chromium element is Cppm based on the mass of the negative electrode current collector, 10≤C≤300;

[0049] A groove is provided on the surface of the negative electrode active layer away from the negative electrode current collector, and the depth of the groove is H μm;

[0050] The electrolyte includes 1,4-dicyano-2-butene. Based on the mass of the electrolyte, the content of the 1,4-dicyano-2-butene is E, 0.01%≤E≤5%; and the following conditions are satisfied: 0.0005≤E*H≤1.75.

[0051] The present application has found that when the chromium content in the negative electrode collector is in the range of 10-300ppm, the negative electrode collector can be ensured to have good conductivity and corrosion resistance; on this basis, by adjusting the groove depth H on the negative electrode sheet and the content E of the electrolyte additive 1,4-dicyano-2-butene to meet E*H in the range of 0.0005-1.75, on the one hand, the rate of oxidation corrosion of the negative electrode collector can be slowed down, the tensile strength of the negative electrode collector can be improved, and the negative electrode collector can be prevented from breaking; on the other hand, it can also ensure that the battery has a higher rate and high temperature cycle performance.

[0052] If the content of 1,4-dicyano-2-butene in the electrolyte is too high, the corrosion effect on the negative electrode current collector is greater. At this time, it is necessary to control the groove on the negative electrode sheet to be shallower, that is, to reduce the H value. On the contrary, if the content of 1,4-dicyano-2-butene in the electrolyte is too low, although it is not conducive to improving the high-temperature cycle performance of the battery, it has less corrosion effect on the negative electrode current collector. At this time, the groove on the negative electrode sheet can be made deeper, that is, the H value needs to be increased, which is conducive to electrolyte infiltration and improves the battery rate performance. It is understandable that the content of 1,4-dicyano-2-butene in the electrolyte and the depth of the groove on the negative electrode sheet cannot be too large at the same time, otherwise it will accelerate the corrosion of the negative electrode current collector and affect the performance of the battery. That is, the groove depth H on the negative electrode sheet is negatively correlated with the content E of the electrolyte additive 1,4-dicyano-2-butene. The value of E*H needs to be controlled within the range of 0.0005-1.75 to take into account the tensile strength of the negative electrode current collector and the high temperature cycle and rate performance of the battery.

[0053] As an example, the content C of chromium in the negative electrode current collector can be, for example, 10ppm, 50ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, etc., or within the range of any two of the above values. The content E of 1,4-dicyano-2-butene in the electrolyte can be 0.01%, 0.1%, 0.25%, 0.5%, 0.75%, 1%, 2.5%, 4.3%, 5%, etc., or within the range of any two of the above values. The value of E*H can be 0.0005, 0.005, 0.05, 0.1, 0.5, 1, 1.5, 1.75, etc., or within the range of any two of the above values.

[0054] Further research found that when the product E*H of the groove depth H on the negative electrode sheet and the content E of 1,4-dicyano-2-butene in the electrolyte is in the range of 0.005-1.5, it can more effectively slow down the rate of oxidation corrosion of the negative electrode collector, prevent the negative electrode collector from breaking, and ensure the rate and high-temperature cycle performance of the battery. In particular, when the content E of 1,4-dicyano-2-butene in the electrolyte is in the range of 0.1%-4.3%, it can not only improve the lattice stability of the positive electrode material, but also will not cause excessive corrosion to the negative electrode collector, which is conducive to maintaining the strength of the negative electrode collector without reducing, thereby ensuring the performance of the battery.

[0055] In some embodiments, the groove depth H on the negative electrode sheet is 5 μm-35 μm, and as an example, it can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, etc., or within the range of any two of the above values. This can ensure the electrolyte's wetting effect on the negative electrode sheet, reduce the polarization of the negative electrode side, reduce the battery's internal resistance, and ensure good rate performance; on the other hand, it will not cause excessive damage to the negative electrode current collector, which is conducive to maintaining a high tensile strength of the negative electrode current collector, thereby ensuring the performance of the battery.

[0056] The present application found that when the ratio C / E of the chromium content in the negative electrode current collector to the 1,4-dicyano-2-butene content in the electrolyte falls within the range of 200-3×10 6 When it is within this range, the conductivity of the negative electrode collector can be ensured while preventing the electrolyte from corroding the negative electrode collector, thereby ensuring the battery's rate and high-temperature cycle performance.

[0057] If the chromium content in the negative electrode current collector is high, it means that the corrosion resistance of the negative electrode current collector is good. At this time, the content of 1,4-dicyano-2-butene additive in the electrolyte can be appropriately increased to improve the stability of the negative electrode sheet and the high temperature cycle performance of the battery; conversely, if the chromium content in the negative electrode current collector is low, it means that the corrosion resistance of the negative electrode current collector is poor. At this time, the content of 1,4-dicyano-2-butene additive in the electrolyte should be appropriately reduced to ensure that the negative electrode current collector can meet the strength requirements, thereby ensuring the performance of the battery.

[0058] As an example, the value of C / E may be 200, 233, 600, 1000, 5000, 10000, 50000, 100000, 500000, 1000000, 3000000, etc. or within a range formed by any two of the above values. In particular, when C / E falls within 233-10 5 When it is within this range, it can more effectively ensure that the negative electrode current collector has a higher tensile strength, and the battery has better rate and high-temperature cycle performance.

[0059] In a wound lithium-ion secondary battery, the core is formed by winding a positive electrode sheet, a negative electrode sheet, and a separator between the positive and negative electrode sheets. In some embodiments, the plan view and partial cross-sectional view of the negative electrode sheet are as follows: Figure 1 , Figure 2 See Figure 1 and Figure 2, a recessed area with an opening toward the separator is provided at the middle position of the negative electrode sheet, and the recessed area includes a tab groove 4 and a tab paper groove 6; along the thickness direction (z direction) of the negative electrode sheet, the tab paper groove 6 is higher than the tab groove 4 to form a step surface 7, and a tab paper (not shown in the figure) is provided on the step surface 7, and the tab paper covers the tab groove 4. In the thickness direction of the negative electrode sheet, the thickness T3 of the negative electrode active layer ≥ the depth T1 of the tab paper groove, and the depth T1 of the tab paper groove ≥ the thickness T2 of the tab protective paper.

[0060] It is understandable that the pole ear 5 is welded in the pole ear slot 4, so that a welding point protrusion will be formed at the pole ear welding point. In order to prevent the pole ear protrusion from piercing the diaphragm and causing a short circuit, the usual practice is to paste the pole ear tape at the opening of the pole ear slot to isolate the contact between the welding point protrusion and the diaphragm. However, due to the thickness of the pole ear tape itself, the pole piece will be raised, and after winding, a bridge mode will be formed with the diaphragm, resulting in a longer interface path for lithium ions to be conducted here, an increase in impedance, and it is also easy to cause poor interface phenomena such as bubbles and pores, which triggers lithium deposition during battery charging. Therefore, the present application adopts a step-by-step glue embedding technology to embed the pole ear tape in the negative electrode active layer to offset the sacrifice of the cell thickness caused by the thickness of the tape, so as to achieve the purpose of improving the energy density of the cell.

[0061] Furthermore, in some embodiments, in the length direction (x direction) of the negative electrode sheet, the width W1 of the tab tape groove is ≥ the width W2 of the tab tape, and the width W2 of the tab tape is ≥ the width S of the tab groove. In this way, the flatness of the tab tape can be ensured, so that the tab tape can completely cover the exposed copper foil in the tab groove to prevent the copper foil current collector from being oxidized and corroded by the electrolyte.

[0062] In order to prevent the exposed copper foil current collector in the tab groove from reducing its strength after absorbing heat due to the large range of laser heat radiation during laser scribing, in some embodiments of the present application, see Figure 3 It is necessary to ensure that the distance G1 between the groove and the edge of the tab groove (i.e. the junction of the tab groove and the negative electrode active layer) is greater than 0 and less than or equal to 5 mm. As an example, it can be 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, etc. or within the range formed by any two of the above values.

[0063] It is understandable that the width of the negative electrode active layer is smaller than the width of the negative electrode current collector, thereby forming an empty foil area in the width direction (y direction) of the negative electrode current collector, that is, an exposed copper foil current collector. In order to prevent the exposed copper foil current collector in the empty foil area from losing strength after absorbing heat due to the large range of laser heat radiation during laser scribing, in some embodiments of the present application, it is necessary to ensure that the length of the groove is smaller than the width of the negative electrode active layer. See Figure 3For example, the distance between the two ends of the groove (the distance between the two ends is the groove length) and the edge of the negative electrode active layer adjacent to the end is G2 greater than 0 and less than or equal to 5 mm. As an example, it can be 0.1 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, etc. or within the range formed by any two of the above values.

[0064] In some embodiments, in combination Figure 1 and Figure 3 The grooves on the negative electrode sheet can be either linear or curved. For ease of processing, linear grooves are often used. The number of grooves can be 1, 2, 3 or more. In order to take into account the battery performance, multiple grooves are usually required. They can be evenly spaced or irregularly spaced. Taking into account the convenience of processing, in this application, multiple grooves are evenly spaced, and the spacing between two adjacent grooves is L, satisfying 0.5mm≤L≤2mm. As an example, the spacing L of the grooves can be 0.5mm, 1mm, 1.5mm, 2mm, etc. or within the range of any two of the above values; at the same time, each groove can be distributed extending along the width direction of the negative electrode sheet.

[0065] The present application has found that when the width S of the tab groove (along the length direction of the negative electrode sheet) and the spacing L of the grooves satisfy 3≤S / L≤30, the exposed copper foil in the tab groove can be reduced from being affected by laser radiation, thereby preventing insufficient tab welding or damage to the negative electrode current collector after welding. In some embodiments, the width S of the tab groove is in the range of 6mm-15mm, and as an example, it can be 6mm, 8mm, 10mm, 12mm, 15mm, etc., or in the range of any two of the above values; the ratio S / L between the width of the tab groove and the spacing L of the grooves can be 3, 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, 30, etc., or in the range of any two of the above values.

[0066] To optimize battery performance, the negative electrode paste may be coated using a double-layer coating technique. Therefore, in some embodiments of the present application, the negative electrode active layer includes a first active layer and a second active layer stacked together, and the first active layer is located between the negative electrode current collector and the second active layer.

[0067] The first active layer includes a first negative electrode active material, the first negative electrode active material includes a first graphite, and the median particle size Dv501 of the first graphite is 12μm-20μm, as an example, it can be 12μm, 14μm, 16μm, 18μm, 20μm, etc., or within the range of any two of the above values. The second active layer includes a second negative electrode active material, the second negative electrode active material includes a second graphite, the median particle size Dv502 of the second graphite is 5μm-12μm, as an example, it can be 5μm, 7μm, 9μm, 10μm, 11μm, 12μm, etc., or within the range of any two of the above values, and the median particle size Dv501 of the first graphite is greater than the median particle size Dv502 of the second graphite.

[0068] It should be noted that the median particle size Dv501 of the first graphite and the median particle size Dv502 of the second graphite can both be obtained by testing with a laser particle size analyzer.

[0069] The present application has found that the second active layer located on the surface of the negative electrode sheet includes small-particle graphite, which is beneficial to the infiltration of the electrolyte and the deintercalation of lithium ions. This increases the risk of corrosion of the negative electrode collector while improving the battery charge and discharge rate. Therefore, on the one hand, the present application controls the ratio x of the thickness of the second active layer to the total thickness of the negative electrode active layer to satisfy 0.1≤x≤0.5, so as to take into account the battery's rate performance and the tensile strength of the copper foil. On the other hand, a first active layer including large-particle graphite is arranged under the second active layer. Compared with small-particle graphite, large-particle graphite has better structural stability, which is beneficial to the battery's cycle performance. In addition, through the particle size grading of large / small-particle graphite, the compaction density of the negative electrode sheet can also be improved, further improving the problem of easy corrosion of the negative electrode collector, thereby ensuring the performance of the battery.

[0070] As an example, the value of the ratio x of the thickness of the second active layer to the total thickness of the negative electrode active layer may be, for example, 0.1, 0.2, 0.2, 0.4, 0.5, etc., or be within the range of any two of the above values.

[0071] Furthermore, when the ratio x of the thickness of the second active layer to the total thickness of the negative electrode active layer, the content E of the 1,4-dicyano-2-butene additive in the electrolyte, the first graphite median particle size Dv501 and the second graphite median particle size Dv502 satisfy: 200≤(x*Dv502+(1-x)*Dv501) / E≤190000, the tensile strength of the copper foil can be guaranteed while taking into account the battery rate and cycle performance, thereby ensuring the performance of the battery.

[0072] As an example, the value of (x*Dv502+(1-x)*Dv501) / E can be 200, 1000, 5000, 10000, 25000, 50000, 75000, 100000, 150000, 190000, etc., or be within the range of any two of the above values.

[0073] It is understandable that the silicon negative electrode has the advantages of high gram capacity and high energy density. When used in the lithium-ion secondary battery of the present application, it can significantly improve the energy density of the battery cell. Specifically, in some embodiments of the present application, the first negative electrode active material and / or the second negative electrode active material also include a silicon-based material. Based on the mass of the first negative electrode active material or the second negative electrode active material, the content of the silicon-based material is D, 1%≤D≤30%. As an example, the amount of silicon-based material added can be, for example, 1%, 3%, 7%, 10%, 15%, 20%, 25%, 30% or within the range of any two of the above values.

[0074] The present application has found that when the content D of the silicon-based material and the content E of the 1,4-dicyano-2-butene additive in the electrolyte satisfy 0.2≤D / E≤3000, especially 0.7≤D / E≤300, the stability of the negative electrode material can be further ensured on the basis of preventing the corrosion of the copper foil, thereby improving the cycle and safety performance of the battery. As an example, the value of D / E can be 0.2, 0.7, 2, 10, 50, 100, 200, 300, 500, 1000, 3000, etc. or within the range of any two of the above values.

[0075] It should be noted that the charging cut-off voltage of the lithium-ion secondary battery provided in the present application is ≥4.48V, which is higher than the upper charging limit voltage of conventional lithium-ion secondary batteries, making the lithium-ion secondary battery of the present application more advantageous in terms of energy density, service life and power performance.

[0076] The present application is described in further detail below in conjunction with specific examples, and these examples should not be construed as limiting the scope of protection claimed in the present application. Where specific experimental steps or conditions are not indicated in the examples and comparative examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. Where the reagents or instruments used do not indicate the manufacturer, they are all conventional reagent products that can be obtained commercially. In all examples and comparative examples of the present application, the unit % represents the mass percentage content.

[0077] Example 1

[0078] Step 1: Preparation of positive electrode

[0079] Lithium cobalt oxide, conductive carbon black (SP), and polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 97.6:1.4:1, and N-methylpyrrolidone (NMP) was added and stirred evenly to prepare a positive electrode slurry.

[0080] The positive electrode slurry is coated on the front and back surfaces of the aluminum foil. After baking and rolling, a positive electrode sheet with a thickness of 80 μm is obtained. The positive electrode sheet has a slot of a fixed size. The aluminum electrode tab is laser welded in the slot to obtain a positive electrode sheet containing the aluminum electrode tab.

[0081] Step 2: Preparation of negative electrode

[0082] The first negative electrode active material is mixed with SP, carboxymethyl cellulose lithium (CMC-Li), and styrene-butadiene rubber (SBR) in a mass ratio of 97:0.4:0.1:2.5, and deionized water is added to prepare a first negative electrode slurry; wherein the first negative electrode active material is silicon-carbon doped graphite, the graphite particle size Dv501 is 13μm, the weight of silicon and carbon accounts for 5% of the total weight of the first negative electrode active material, and the silicon content of the silicon-carbon particles is 50%.

[0083] The second negative electrode active material is mixed with SP, CMC-Li, and polyacrylic acid (PAA) in a mass ratio of 97:0.4:0.1:2.5, and deionized water is added to prepare a second negative electrode slurry; wherein the second negative electrode active material is silicon-carbon doped graphite, the graphite particle size Dv502 is 8μm, the weight of silicon and carbon accounts for 5% of the total weight of the second negative electrode active material, and the silicon content of the silicon-carbon particles is 50%.

[0084] The first negative electrode slurry is applied to the two surfaces of the chrome-plated copper foil, and the Cr element content of the copper foil is 100ppm. Then the second negative electrode slurry is applied to the surface of the first negative electrode slurry. After baking and rolling, a negative electrode sheet with a thickness of 95μm is obtained. The negative electrode sheet has a tab slot with a width S=9mm, and its depth is the thickness of the single-sided negative electrode active layer T3=45μm. The copper-plated nickel tab with a width of 6mm is laser welded in this slot. The tab surface is affixed with protective glue, the protective glue width W2=12mm, the protective glue thickness T2=12μm, and the protective glue is accommodated in the tab glue slot. The projection of the tab slot on the copper foil falls within the projection range of the tab glue slot on the copper foil. The depth of the tab glue slot is T1=15μm, and the width of the tab glue slot is W1=14mm.

[0085] A laser is used to scribe the surface of the negative electrode sheet to form multiple grooves arranged at equal intervals, with a groove spacing L = 1.2 mm, a groove depth H = 15 μm, a reserved distance G1 = 0.5 mm between the end of the groove and the edge of the pole lug groove, and a reserved distance G2 = 0.5 mm between the two ends of the groove and the edge of the negative electrode active layer.

[0086] Step 3: After the positive and negative electrode sheets are cut and sliced, they are wound with the diaphragm to obtain a roll core.

[0087] Step 4: The core is packaged, baked, injected, formed, sealed again, sorted and OCV is performed to obtain a lithium-ion battery; wherein the electrolyte is a conventional electrolyte available on the market, the lithium salt in the electrolyte is LiFP6, and the additive 1,4-dicyano-2-butene is added in an amount of 1%.

[0088] The preparation methods of Example 2-6 and Example 1-1 to Example 1-26 are basically the same as Example 1, and the differences are shown in Table 1 and Table 2. Among them, E is the content of 1,4-dicyano-2-butene in the electrolyte, H is the depth of the groove on the negative electrode sheet, C is the content of chromium in the chrome-plated copper foil, L is the spacing of the grooves on the negative electrode sheet, S is the width of the tab groove on the negative electrode sheet, D is the silicon content in the negative electrode active material, Dv501 is the median particle size of graphite in the first active layer, Dv502 is the median particle size of graphite in the second active layer, and x is the ratio of the thickness of the second active layer to the total thickness of the negative electrode active layer.

[0089] Table 1

[0090]

[0091]

[0092] Table 2

[0093]

[0094]

[0095] Test Case

[0096] 1. Particle size test

[0097] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, soaked in dimethyl carbonate (DMC) solvent for 12 hours, and then rinsed with DMC to remove the lithium salt attached to the plate. The negative electrode active layer is then rinsed off the plate with deionized water, and the filtrate is removed by centrifugation after ultrasonication and then dried, and measured using a Malvern particle size tester.

[0098] The test steps are as follows: the negative electrode active layer material is dispersed in deionized water containing a dispersant nonylphenol polyoxyethylene ether (content 0.02-0.03 wt%) to form a mixture, the mixture is ultrasonicated for 2 minutes, and then placed in a Malvern particle size tester for testing.

[0099] Among them, the median particle size of the second graphite is obtained by testing the negative electrode powder within 10 μm thickness of the upper layer of the electrode plate; the median particle size of the first graphite is obtained by testing the negative electrode powder within 20 μm thickness of the lower layer of the electrode plate.

[0100] 2. Silicon-based material content test

[0101] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, soaked in DMC for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate. After drying, the plate is treated at high temperature in an inert atmosphere of a 400°C tubular furnace for 2 hours. The negative electrode active layer can be peeled off from the current collector and the negative electrode active material can be collected.

[0102] In the silicon content test, a TGA 550 thermogravimetric analyzer is used, and the sample size for the test is 5 to 15 mg. In an air or oxygen atmosphere, the temperature is raised from room temperature to 900°C at a rate of 10°C / min, and the temperature is kept at 900°C for 40 minutes, so that the non-silicon components in the negative electrode active material can be volatilized and the silicon can be fully oxidized to silicon dioxide. The weight percentage at the end of the entire test process is the ash content of the negative electrode active material. The ash value is divided by the molar mass of silicon dioxide (60) and then multiplied by the molar mass of silicon (28) to obtain the percentage of silicon in the negative electrode active material.

[0103] 3. Test of chromium content on negative electrode current collector

[0104] The Cr element concentration in the standard solution was measured according to the test method in GBT 30902-2014, in ppm, which is the chromium content on the negative electrode current collector.

[0105] 4. Groove depth and groove spacing test

[0106] After the lithium-ion secondary battery was discharged to 0% SOC, the negative electrode was disassembled and taken out, and then immersed in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the electrode, and tested using a 3D profilometer.

[0107] 5. Battery internal resistance test

[0108] Charge the battery to 50% SOC at a 0.5C rate and test it using an AC resistance meter or a multimeter.

[0109] 6. Rate performance test

[0110] After keeping in a constant temperature room at 25℃ for 2h, use 0.2C constant current to discharge to 3.0V, let it rest for 5min, then use 3C constant current to charge to 4.2V, switch to 2.5C constant current to charge to 4.25V, switch to 2C constant current to charge to 4.48V (1.2C cutoff), record the time of 3C constant current charging to 4.2V, and set the blue electricity tester to record the time every 1s.

[0111] 7. Copper foil tensile strength test

[0112] After the lithium-ion secondary battery is discharged to 0% SOC, the negative electrode plate is disassembled and taken out, and the empty copper foil at the head is taken out, and it is soaked in dimethyl carbonate (DMC) solvent for 12 hours and then rinsed with DMC to remove the lithium salt attached to the plate. After drying, the negative electrode current collector is cut into test samples with a width of 15 mm and a length of more than 50 mm using a cutter; a WD-D3 electronic universal testing machine (with a precision of 0.5 level and an accuracy of ±1% of the indicated value) is used, with a gauge length of 50 mm and a speed of 50 mm / min, and a tensile test is performed on the test sample to measure the tensile strength of the copper foil.

[0113] 8. 45℃ high temperature cycle capacity retention test

[0114] After standing in a constant temperature room at 45℃ for 2h, charge at 3C constant current to 4.2V, then charge at 2C constant current and constant voltage to 4.48V, cut off at 0.05C, stand for 10min, discharge at 0.7C to 3.0V, and cycle 500T in this way. The discharge capacity is C1, and the discharge capacity in the first cycle is C0. C1 / C0 is the capacity retention rate after cycling 500T.

[0115] The above test results are shown in Table 1-3.

[0116] Table 3

[0117]

[0118]

[0119] It can be seen from Tables 1 to 3 that, compared with Comparative Examples 1-2, the internal resistance of the batteries in all embodiments does not exceed 34 mΩ, the time required for 3C constant current charging to 4.2V is not less than 1.2 min, the 45°C high temperature cycle capacity retention rate is above 70%, and the copper foil tensile strength is not less than 490 MPa, which shows that the lithium-ion secondary battery of the present application can effectively improve the tensile strength of the negative electrode current collector while improving the high temperature cycle and rate performance. It should be noted that the smaller the internal resistance of the battery, the longer the high rate charging time, that is, the faster it is fully charged, the better the rate performance.

[0120] Compared with Example 1, the content of 1,4-dicyano-2-butene in the electrolyte of the battery of Example 1-3 is relatively low, resulting in poor effect of improving the lattice stability of the positive electrode material. Lattice collapse is prone to occur during high-temperature cycling, causing irreversible damage to the positive electrode, and thus relatively poor high-temperature cycling performance; at the same time, the groove depth on the negative electrode sheet of Example 1-3 is relatively small, resulting in greater polarization on the negative electrode side, resulting in a larger overall internal resistance of the battery cell and worse rate performance; but at the same time, it also reduces the contact between the electrolyte and the copper foil, thereby reducing the corrosion of the copper foil and ensuring the tensile strength of the copper foil. The situation of Example 1-6 is just the opposite of Example 1-3, so Example 1-6 has good rate and high-temperature cycling performance, and at the same time, the tensile strength of the copper foil is significantly reduced but can still meet the requirements.

[0121] It should be noted that the tensile strength test result of the copper foil is above 480MPa, indicating that the negative electrode current collector has good corrosion resistance and is not prone to band breakage during battery cycling.

[0122] Compared with Example 1, the chromium content in the negative electrode current collector of Example 1-7 is relatively low, which is conducive to reducing the current collector resistance, thereby reducing the overall internal resistance of the battery and optimizing the rate performance. At the same time, the content of 1,4-dicyano-2-butene in the electrolyte is relatively high, which is conducive to the high-temperature cycle performance of the battery. However, due to the small ratio of chromium content to 1,4-dicyano-2-butene content, although it is not conducive to the copper foil to maintain a high tensile strength, it can meet the requirements after practical testing. The situation of Example 1-11 is just the opposite of Example 1-7, so that the rate and high-temperature cycle performance of Example 1-11 are poor, but the tensile strength of the copper foil is high.

[0123] Compared with Example 1, the groove spacing L on the negative electrode sheet of Example 1-17 is larger, and the negative electrode tab groove width S is smaller, so that the ratio of the negative electrode tab groove width S to L is too small, the grooves are sparse, the improvement effect on the polarization of the negative electrode side is poor, and the conductivity of the negative electrode side is reduced, resulting in an increase in the internal resistance of the battery, affecting the rate performance. The situation of Example 1-18 is just the opposite of Example 1-17, so the battery of Example 1-18 has a smaller internal resistance and better rate performance, but due to the dense grooves, the tensile strength of the copper foil is reduced.

[0124] Compared with Example 1, the negative electrode sheet of Example 1-22 has a small amount of silicon doping, which is beneficial to reducing the internal resistance of the battery and optimizing the rate performance. At the same time, due to the small number of side reactions, the high-temperature capacity retention rate is high, and the content of 1,4-dicyano-2-butene in the electrolyte is low, which is beneficial to ensure the tensile strength of the copper foil. However, the negative electrode sheet of Example 1-23 has a high amount of silicon doping. Due to the high strength and high expansion of silicon-based materials, the copper foil will be damaged, resulting in a decrease in the tensile strength of the copper foil, and it is also not conducive to high-temperature cycle performance.

[0125] Compared with Example 1, the graphite particle size in the negative electrode sheet of Example 1-26 is smaller and has good conductivity, so the internal resistance of the battery is smaller and the rate performance is better. At the same time, the content of 1,4-dicyano-2-butene in the electrolyte is high, so the high-temperature cycle performance is good but the tensile strength of the copper foil is low. The graphite particle size in the negative electrode sheet of Example 1-27 is larger, which affects the conductivity, so the internal resistance of the battery is larger, which affects the rate performance. At the same time, the content of 1,4-dicyano-2-butene in the electrolyte is low, which is conducive to ensuring the tensile strength of the copper foil but not conducive to high-temperature cycle performance.

[0126] Compared with Example 1, the content of 1,4-dicyano-2-butene in the electrolyte of the battery of Comparative Example 1 is too low, which makes the value of E*H too small. Although the tensile strength of the copper foil is guaranteed, the high-temperature cycle performance of the battery is seriously affected. At the same time, due to the small depth of the groove on the negative electrode sheet, the electrolyte infiltration effect is poor, which deteriorates the rate performance. On the other hand, in Comparative Example 2, the content of 1,4-dicyano-2-butene in its electrolyte is too high, which makes the value of E*H too large, and the copper foil is severely corroded, resulting in the tensile strength of the copper foil being too low, which cannot meet the requirements, and is also not conducive to the performance of the battery, resulting in poor rate and high-temperature cycle performance of the battery.

[0127] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A lithium-ion secondary battery, comprising a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte; characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector; The negative electrode current collector includes a chromium element, and the content of the chromium element is Cppm based on the mass of the negative electrode current collector, 10≤C≤300; A groove is provided on the surface of the negative electrode active layer away from the negative electrode current collector, and the depth of the groove is H μm; The electrolyte includes 1,4-dicyano-2-butene, and the content of the 1,4-dicyano-2-butene is E, 0.01%≤E≤5%, based on the mass of the electrolyte; Satisfies: 0.0005≤E*H≤1.

75.

2. The lithium ion secondary battery according to claim 1, characterized in that: Satisfies: 0.005≤E*H≤1.5; and / or, 5≤H≤35.

3. The lithium ion secondary battery according to claim 1 or 2, characterized in that: Satisfy: 200≤C / E≤3×10 6 .

4. The lithium ion secondary battery according to claim 3, characterized in that: At least one of the following conditions is met: a. 10≤C≤100; b. 0.1% ≤ E ≤ 4.3%; c、233≤C / E≤10 5 。 5. The lithium ion secondary battery according to claim 1, 2 or 4, characterized in that: The negative electrode sheet is provided with a recessed area with an opening toward the diaphragm, and the recessed area includes a tab groove and a tab paper groove; along the thickness direction of the negative electrode sheet, the tab paper groove is higher than the tab groove to form a step surface, and the tab paper is provided on the step surface, and the tab paper covers the tab groove; In the thickness direction of the negative electrode sheet, the thickness T3 of the negative electrode active layer is greater than or equal to the depth T1 of the tab tape groove, and the depth T1 of the tab tape groove is greater than or equal to the thickness T2 of the tab protective tape; And / or, in the length direction of the negative electrode sheet, the width W1 of the tab tape groove is ≥ the width W2 of the tab tape, and the width W2 of the tab tape is ≥ the width S of the tab groove.

6. The lithium ion secondary battery according to claim 5, characterized in that: The length direction of the groove is parallel to the width direction of the negative electrode sheet, the number of the grooves is at least 2, and the distance between two adjacent grooves is L, 0.5 mm ≤ L ≤ 2 mm; The width S of the tab groove satisfies: 6mm≤S≤15mm, and 3≤S / L≤30.

7. The lithium ion secondary battery according to claim 5, characterized in that: The distance between the junction of the tab groove and the negative electrode active layer and the groove is G1, 0<G1≤5mm; And / or, the distance between the end of the groove and the edge of the negative electrode active layer is G2, 0<G2≤5mm.

8. The lithium ion secondary battery according to claim 1, 2 or 4, characterized in that: The negative electrode active layer comprises a first active layer and a second active layer which are stacked, the first active layer is located between the negative electrode current collector and the second active layer, and the ratio of the thickness of the second active layer to the total thickness of the negative electrode active layer is x, 0.1≤x≤0.5; The first active layer includes a first negative electrode active material, the first negative electrode active material includes a first graphite, and the median particle size Dv501 of the first graphite is 12 μm-20 μm; The second active layer includes a second negative electrode active material, the second negative electrode active material includes a second graphite, and the median particle size Dv502 of the second graphite is 5 μm-12 μm; Satisfies: Dv501>Dv502.

9. The lithium ion secondary battery according to claim 8, characterized in that: The first negative electrode active material and / or the second negative electrode active material further comprises a silicon-based material. Based on the mass of the first negative electrode active material or the second negative electrode active material, the content of the silicon-based material is D, and satisfies: 0.2≤D / E≤3000, 0.01%≤E≤5%; Preferably, the D is 1%-30%; Preferably, the D is 3%-30%, the E is 0.1%-4.3%, and 0.7≤D / E≤300.

10. The lithium ion secondary battery according to any one of claims 1, 2, 4, 6, 7 or 9, characterized in that: The charging cut-off voltage of the lithium-ion secondary battery is ≥4.48V.

Citation Information

Patent Citations

  • Pole piece and battery

    CN112750978A

  • Secondary battery and electronic device

    CN117716543A

  • Battery

    CN118213623A

  • Electrochemical device and electronic device

    CN118435396A

  • Negative plate and lithium ion secondary battery

    CN118630134A

Cited By

  • Negative active material, negative active material coating, negative pole piece, cylindrical lithium ion battery and electric device

    CN121149206A

  • Lithium ion battery

    CN122202452A